Access to public transport and childhood obesity: A systematic review. (30th January 2020) - Xu, Fei; Jin, Lingling; Qin, Zhenzhen; Chen, Xiang; Xu, Zhen; He, Jing; Wang, Zhiyong; Ji, Wen; Ren, Fu; Du, Qingyun; Xiong, Yaqing; Jia, Peng
Summary: The lack of access to public transport is generally considered to be a risk factor for childhood obesity by discouraging active transport and thus physical activity. To explore the association between access to public transport and childhood obesity, we have conducted a systematic literature search in the Cochrane Library, PubMed, and Web of Science for studies published before January 1, 2019. A total of 25 cross‐sectional and two longitudinal studies conducted in 10 countries were identified. Inconsistent findings were identified arising from a great variety of sample characteristics, definitions of exposure (ie, access to public transport), and outcome variables (eg, obesity), and analysis methods. While over half of the studies showed null associations between access to public transport and childhood obesity, we have observed more positive than negative associations among the rest of the studies. These observations suggest that an increased level of access to public transport may have a health‐promoting effect and hence prevent the development of childhood obesity. However, this conclusion needs to be further corroborated in future research on the basis of large‐sample health surveys, in situ observations, and comparative analyses among different study areas.